Ultrasound-guided genitofemoral nerve block for inguinal hernia repair in the male adult: a randomized controlled pilot study. - Frassanito, Luciano; Zanfini, Bruno A; Pitoni, Sara; Germini, Paolo; Del Vicario, Miryam; Draisci, Gaetano (Minerva Anestesiol, 2018)
BACKGROUND: Ultrasound-guided (USG) ilioinguinal/iliohypogastric nerve (II/IHN) block is a widely validated anesthetic technique for inguinal herniorrhaphy. As the spermatic cord, scrotum, and adjacent thigh receive sensory innervation from the genital branch of genitofemoral nerve (GFN), the addition of GFN block has been suggested to improve the quality of perioperative anesthesia and analgesia. The aim of this study is to compare GFN block plus II/IHN block with II/IHN block alone for intraoperative anesthesia and post-operative pain management. METHODS: We enrolled 80, ASA I-III, male adults scheduled for elective open herniorrhaphy. Patients were randomized to receive either USG II/IHN plus GFN block (Case Group) or USG II/IHN block alone (Control Group). The outcome measures were the assessment of postoperative VAS scores on coughing and the adequacy of anesthesia, measured with intraoperative requirement for extra local anesthetic (LA) infiltration and number of patients needing systemic sedation. RESULTS: The requirement of intraoperative additional doses of LA was significantly lower in the Case Group (median LA volume administered by the surgeon: 13.8±5.6 mL vs. 20.7±9.1 mL, P<0.05). Two patients in the Control Group needed systemic sedation. VAS scores at 15 minutes, 30 minutes, 1 hour, 2 hours, pre-discharge, and 24 hours were significantly lower in the Case Group (P<0.005). Four cases of femoral nerve block were reported, three in the Control Group, one in the Case Group (2.2% vs. 7.7%, P>0.05). CONCLUSIONS: The combination of GFN block and II/IHN block is associated with lower postoperative VAS scores and lower doses of intraoperative additional LA.

An unusual unilateral breast enlargement in a prepubertal girl. - Pavan, Matteo; Faleschini, Elena; Tornese, Gianluca; Zandonà, Lorenzo; Ventura, Alessandro (Arch Dis Child, 2018)

An Update on the Pathogenesis and Treatment of Chronic Recurrent Multifocal Osteomyelitis in Children. - Taddio, Andrea; Zennaro, Floriana; Pastore, Serena; Cimaz, Rolando (Paediatr Drugs, 2017)
Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic non-bacterial osteomyelitis (CNO), is a rare inflammatory disorder that primarily affects children. It is characterized by pain, local bone expansion, and radiological findings suggestive of osteomyelitis, usually at multiple sites. CRMO predominantly affects the metaphyses of long bones, but involvement of the clavicle or mandible are suggestive of the diagnosis. CRMO is a diagnosis of exclusion, and its pathogenesis remains unknown. Differential diagnosis includes infection, malignancies, benign bone tumors, metabolic disorders, and other autoinflammatory disorders. Biopsy of the bone lesion is not often required but could be necessary in unclear cases, especially for differentiation from bone neoplasia. Non-steroidal anti-inflammatory drugs (NSAIDs) are the first-line treatment. Alternative therapies have been used, including corticosteroids, methotrexate, bisphosphonates, and tumor necrosis factor (TNF)-α inhibitors. No guidelines have been established regarding diagnosis and treatment options. This manuscript gives an overview of the most recent findings on the pathogenesis of CRMO and clinical approaches for patients with the condition.
Keywords: Adrenal Cortex Hormones; Anti-Inflammatory Agents, Non-Steroidal; Child; Chronic Disease; Diagnosis, Differential; Humans; Osteomyelitis; Recurrence; Tumor Necrosis Factor-alpha

Understanding the role of personality and alexithymia in food preferences and PROP taste perception. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; La Bianca, Martina; Gasparini, Paolo; Carlino, Davide; Tepper, Beverly J (Physiol Behav, 2016)
Taste perception and food preferences are influenced by a variety of factors, including personality characteristics. The aims of this study were to examine the role of personality characteristics, such as alexithymia (a personality construct characterized by inability to identify, describe, and work with one's own feelings), in: 1) taste responses to the bitter genetic taste-marker PROP and 2) food liking. We studied 649 healthy subjects residing in six genetically-isolated villages of Northeast Italy. Data on PROP taste responsiveness, food liking, personality characteristics and TAS2R28 genotypes were collected. Results showed that PROP non-tasters had higher alexithymia scores than PROP tasters. Moreover, the presence of alexithymia in heterozygous individuals for the rs1726886 polymorphism of the TAS2R38 gene was associated with a reduction in the perceived intensity of PROP. Finally, higher alexithymia scores were associated with liking of alcohol, sweets and fats/meats whereas lower alexithymia scores were related to liking of vegetables, condiments and strong cheeses, Measures of temperament, character, anxiety and depression were also related to food liking. Our findings suggest that: 1) alexithymia, in addition to the TAS2R38 polymorphism, may play a role in responsiveness to the aversive and bitter taste of PROP; and 2) alexithymia, in combination with other personality traits, may provide important insights for better understanding food liking.

Ultrastructural Morphology of Sperm from Human Globozoospermia. - Ricci, Giuseppe; Andolfi, Laura; Zabucchi, Giuliano; Luppi, Stefania; Boscolo, Rita; Martinelli, Monica; Zweyer, Marina; Trevisan, Elisa (Biomed Res Int, 2015)
Globozoospermia is a rare disorder characterized by the presence of sperm with round head, lacking acrosome. Coiling tail around the nucleus has been reported since early human studies, but no specific significance has conferred it. By contrast, studies on animal models suggest that coiling tail around the nucleus could represent a crucial step of defective spermatogenesis, resulting in round-headed sperm. No observations, so far, support the transfer of this hypothesis to human globozoospermia. The purpose of this work was to compare ultrastructural morphology of human and mouse model globozoospermic sperm. Sperm have been investigated by using scanning and transmission electron microscopy. The images that we obtained show significant similarities to those described in GOPC knockout mice, an animal model of globozoospermia. By using this model as reference, we were able to identify the probable steps of the tail coiling process in human globozoospermia. Although we have no evidence that there is the same pathophysiology in man and knocked-out mouse, the similarities between these ultrastructural observations in human and those in the experimental model are very suggestive. This is the first demonstration of the existence of relevant morphological homologies between the tail coiling in animal model and human globozoospermia.

Unusual onset of a case of chronic recurrent multifocal osteomyelitis. - Barrani, M; Massei, F; Scaglione, M; Paolicchi, A; Vitali, S; Ciancia, E M; Crovella, S; Caparello, M C; Consolini, R (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Chronic recurrent multifocal osteomyelitis (CRMO) is a rare condition that commonly affects the clavicle and pelvis. CASE PRESENTATION: We report here a case a 12 years old girl with CRMO arising with recurrent episodes of left supraorbital headache, followed by the appearance of a periorbital dyschromia. Magnetic resonance imaging (MRI) of the skull and orbits revealed an important subacute inflammatory process. Few months after, the child presented a painful swelling of the left clavicle; the histological examination of the related biopsy allowed to establish the diagnosis of CRMO. CONCLUSION: CRMO presenting as acute headache involving neurocranium is rare; to our knowledge this is the first recognized case in the world literature. This pathological condition is frequently misdiagnosed as infection or neoplasm and needs a deep investigation for the differential diagnosis. The physical, laboratoristic and instrumental diagnostic investigations of the patient and the treatment employed are described in detail.

On the use of Chinese population as a proxy of Amerindian ancestors in genetic admixture studies with Latin American populations. - de Moura, Ronald R; de Queiroz Balbino, Valdir; Crovella, Sergio; Brandão, Lucas A C (Eur J Hum Genet, 2015)

Usher syndrome: an effective sequencing approach to establish a genetic and clinical diagnosis. - Lenarduzzi, S; Vozzi, D; Morgan, A; Rubinato, E; D'Eustacchio, A; Osland, T M; Rossi, C; Graziano, C; Castorina, P; Ambrosetti, U; Morgutti, M; Girotto, G (Hear Res, 2015)
Usher syndrome is an autosomal recessive disorder characterized by retinitis pigmentosa, sensorineural hearing loss and, in some cases, vestibular dysfunction. The disorder is clinically and genetically heterogeneous and, to date, mutations in 11 genes have been described. This finding makes difficult to get a precise molecular diagnosis and offer patients accurate genetic counselling. To overcome this problem and to increase our knowledge of the molecular basis of Usher syndrome, we designed a targeted resequencing custom panel. In a first validation step a series of 16 Italian patients with known molecular diagnosis were analysed and 31 out of 32 alleles were detected (97% of accuracy). After this step, 31 patients without a molecular diagnosis were enrolled in the study. Three out of them with an uncertain Usher diagnosis were excluded. One causative allele was detected in 24 out 28 patients (86%) while the presence of both causative alleles characterized 19 patients out 28 (68%). Sixteen novel and 27 known alleles were found in the following genes: USH2A (50%), MYO7A (7%), CDH23 (11%), PCDH15 (7%) and USH1G (2%). Overall, on the 44 patients the protocol was able to characterize 74 alleles out of 88 (84%). These results suggest that our panel is an effective approach for the genetic diagnosis of Usher syndrome leading to: 1) an accurate molecular diagnosis, 2) better genetic counselling, 3) more precise molecular epidemiology data fundamental for future interventional plans.
Keywords: Adult; Alleles; Cadherins; Extracellular Matrix Proteins; Female; Genetic Counseling; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Mutation; Myosins; Nerve Tissue Proteins; Usher Syndromes

An unusual long-term complication of transobturator polypropylene mesh. - Sartore, Andrea; Zennaro, Floriana; Banco, Rubina (Arch Gynecol Obstet, 2014)
Serious complications associated with surgical mesh for transvaginal repair of POP, as infections, vaginal mesh exposure, painful mesh shrinkage and dyspareunia, are not rare. A 48-year-old woman underwent the Perigee procedure because of a stage 3 anterior wall prolapse. Eleven months after surgery, the patient became suddenly unable to walk because of a strong pain to the left thigh root after running. The MRI revealed an external obturator left muscle hyperintensity consistent with muscular oedema; the patient was treated with oral corticosteroids with a complete resolution of the pain. We could hypothesize that the posterior arm of the mesh caused a laceration of the muscles of the obturator space with consequent oedema and pain. The use of the meshes in prolapse surgery can cause unexpected long-term complications.
Keywords: Cystocele; Dyspareunia; Female; Glucocorticoids; Humans; Middle Aged; Pelvic Organ Prolapse; Polypropylenes; Postoperative Complications; Prednisone; Surgical Mesh; Treatment Outcome; Vagina

Unusual splice site mutations disrupt FANCA exon 8 definition. - Mattioli, Chiara; Pianigiani, Giulia; De Rocco, Daniela; Bianco, Anna Monica Rosaria; Cappelli, Enrico; Savoia, Anna; Pagani, Franco (Biochim Biophys Acta, 2014)
The pathological role of mutations that affect not conserved splicing regulatory sequences can be difficult to determine. In a patient with Fanconi anemia, we identified two unpredictable splicing mutations that act on either sides of FANCA exon 8. In patients-derived cells and in minigene splicing assay, we showed that both an apparently benign intronic c.710-5T>C transition and the nonsense c.790C>T substitution induce almost complete exon 8 skipping. Site-directed mutagenesis experiments indicated that the c.710-5T>C transition affects a polypyrimidine tract where most of the thymidines cannot be compensated by cytidines. The c.790C>T mutation located in position -3 relative to the donor site induce exon 8 skipping in an NMD-independent manner and complementation experiments with modified U1 snRNAs showed that U1 snRNP is only partially involved in the splicing defect. Our results highlight the importance of performing splicing functional assay for correct identification of disease-causing mechanism of genomic variants and provide mechanistic insights on how these two FANCA mutations affect exon 8 definition.
Keywords: Base Sequence; Cell Line, Tumor; Codon, Nonsense; Exons; Fanconi Anemia Complementation Group A Protein; HeLa Cells; Humans; Introns; Molecular Sequence Data; Mutagenesis, Site-Directed; Ribonucleoproteins, Small Nuclear; RNA Splice Sites; RNA Splicing

Use of placebo in a trial of thalidomide for pediatric Crohn disease--reply. - Lazzerini, Marzia; Martelossi, Stefano; Ventura, Alessandro (JAMA, 2014)
Keywords: Crohn Disease; Female; Humans; Immunosuppressive Agents; Male; Thalidomide

Under pressure. - De Cunto, Angela; Berti, Irene; Minute, Marta; Longo, Giorgio (Eur J Pediatr, 2013)
Physical urticaria is a rare but challenging subset of chronic urticaria. Wheals of pressure urticaria are typically delayed in appearance. A pressure test can easily be done to confirm the diagnosis.
Keywords: Child; Humans; Male; Pressure; Urticaria

Upper gastrointestinal involvement in paediatric onset Crohn's disease: prevalence and clinical implications. - Crocco, S; Martelossi, S; Giurici, N; Villanacci, V; Ventura, A (J Crohns Colitis, 2012)
BACKGROUND AND AIMS: Our study evaluated the prevalence, the characteristics and implications of the upper gastrointestinal localisation (UGI+) in paediatric Crohn's Disease (CD) patients. METHODS: This prospective study evaluated 45 newly diagnosed CD patients at diagnosis and follow up with respect to CD localisation. RESULTS: All patients presented CD at the colon and/or ileum. In 24/45 patients (53.3%, 12 F and 12 M) an UGI+ involvement was also found. UGI+ patients had a younger age of onset (10.9 years versus 12.6 years; P<0.05). PCDAI at diagnosis was significantly higher in the UGI+ (41 vs. 25 P<0.01). UGI+ patients were overall more symptomatic. Pancolitis and extraintestinal manifestations were also more frequent (19/24 (80%) vs. 12/21 (57%) P<0.01). Growth was more impaired at diagnosis in UGI+ patients. By the end of the follow-up (mean 3 years, range 2 to 4) no significant difference was found in PCDAI (17 in UGI+ patients vs. 11 in UGI- P=NS), or the number of relapses. Weight and growth catch-up in UGI+ patients were comparable to UGI- ones. However, UGI+ patients required a more aggressive therapeutic approach. CONCLUSION: At least half of paediatric onset CD patients have an upper gastrointestinal localisation. UGI+ patients present an earlier onset and a more severe disease. The final outcome does not differ, but UGI+ patients require a more aggressive therapeutic approach.
Keywords: Adolescent; Age of Onset; Child; Crohn Disease; Female; Humans; Male; Prospective Studies; Upper Gastrointestinal Tract

Use of specific antiretroviral regimens among HIV-infected women in Italy at time of conception: 2001-2011. - Floridia, Marco; Ravizza, Marina; Guaraldi, Giovanni; Pinnetti, Carmela; Martinelli, Pasquale; Tamburrini, Enrica (AIDS Patient Care STDS, 2012)
Keywords: Anti-HIV Agents; Drug Administration Schedule; Female; Fertilization; HIV Protease Inhibitors; HIV Seropositivity; Humans; Infectious Disease Transmission, Vertical; Italy; Pregnancy; Reverse Transcriptase Inhibitors; Sentinel Surveillance

An unusual case of buccal obstruction: the antrochoanal polyp. - De Cunto, Angela; Minen, Federico (Arch Dis Child, 2011)
Keywords: Adolescent; Cheek; Female; Humans; Mouth Diseases; Nasal Obstruction; Nasal Polyps; Oropharynx

Use of zidovudine-sparing HAART in pregnant HIV-infected women in Europe: 2000-2009. - Tariq, Shema; Townsend, Claire L; Cortina-Borja, Mario; Duong, Trinh; Elford, Jonathan; Thorne, Claire; Tookey, Pat A (J Acquir Immune Defic Syndr, 2011)
BACKGROUND: Increasing numbers of women in resource-rich settings are prescribed zidovudine (ZDV)-sparing highly active antiretroviral therapy (HAART) in pregnancy. We compare ZDV-sparing with ZDV-containing HAART in relation to maternal viral load at delivery, mother-to-child transmission (MTCT) of HIV, and congenital abnormality. METHODS: This is an analysis of data from the National Study of HIV in Pregnancy and Childhood and the European Collaborative Study. Data on 7573 singleton births to diagnosed HIV-infected women between January 2000 and June 2009 were analyzed. Logistic regression models were fitted to estimate adjusted odds ratios (AORs). RESULTS: Overall, 15.8% (1199 of 7573) of women received ZDV-sparing HAART, with increasing use between 2000 and 2009 (P < 0.001). Nearly a fifth (18.4%) of women receiving ZDV-sparing HAART in pregnancy had a detectable viral load at delivery compared with 28.6% of women on ZDV-containing HAART [AOR 0.90; 95% confidence interval (CI): 0.72 to 1.14, P = 0.4]. MTCT rates were 0.8% and 0.9% in the ZDV-sparing and ZDV-containing groups, respectively (AOR 1.81; 95% CI: 0.77 to 4.26, P = 0.2). The congenital abnormality rate was the same in both groups (2.7%, AOR 0.98; 95% CI: 0.66 to 1.45, P = 0.9), with no significant difference between the groups in a subanalysis of pregnancies with first trimester HAART exposure (AOR 0.79; 95% CI: 0.48 to 1.30, P = 0.4). CONCLUSIONS: We found no difference in risk of detectable viral load at delivery, MTCT, or congenital abnormality when comparing ZDV-sparing with ZDV-containing HAART. With increasing use of ZDV-sparing HAART, continued monitoring of pregnancy outcomes and long-term consequences of in utero exposure to these drugs is required.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Europe; Female; HIV Infections; Humans; Infant; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Retrospective Studies; Time Factors; Viral Load; Zidovudine

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

The universe of immune deficiencies in Crohn's disease: a new viewpoint for an old disease? - Tommasini, Alberto; Pirrone, Angela; Palla, Gabriella; Taddio, Andrea; Martelossi, Stefano; Crovella, Sergio; Ventura, Alessandro (Scand J Gastroenterol, 2010)
Crohn's disease (CD) is generally considered a multifactorial disorder, since different genetic and environmental factors are thought to play a role in its pathogenesis. Recently, genome wide linkage studies allowed to identify the association of several loci with the increased risk of CD, although it is still unclear how they interact with environmental factors in causing the disease. The fact that many CD-risk-related genes are involved in the function of phagocytes seems in agreement with the well known role of these cells in CD histopathology. Functional defects in cytokine production or in clearance of bacteria in CD patients have recently been reported. Growing evidence that CD could arise from primary phagocyte immunodeficiency is also coming from the study of cases with early onset in infancy. We review such evidences starting from selected cases and discuss the clinical implications of these findings.
Keywords: Biological Markers; Crohn Disease; Cytokines; Evidence-Based Medicine; Granulomatous Disease, Chronic; Hematopoietic Stem Cell Transplantation; Humans; Immunosuppressive Agents; Phagocytes; Treatment Outcome; Wiskott-Aldrich Syndrome

Use of ketamine continuous infusion for pediatric sedation in septic shock. - Barbi, Egidio; Rizzello, Elisa; Taddio, Andrea (Pediatr Emerg Care, 2010)
Keywords: Anesthetics, Dissociative; Child; Conscious Sedation; Humans; Infusions, Intravenous; Ketamine; Male; Shock, Septic

Usefulness of the measurement of azathioprine metabolites in the assessment of non-adherence. - Stocco, Gabriele; Londero, Margherita; Campanozzi, Angelo; Martelossi, Stefano; Marino, Sara; Malusà, Noelia; Bartoli, Fiora; Decorti, Giuliana; Ventura, Alessandro (J Crohns Colitis, 2010)
Azathioprine is a thiopurine immunosuppressive antimetabolite used to chronically treat inflammatory bowel disease and autoimmune hepatitis. Azathioprine treatment is a long-term therapy and therefore it is at risk for non-adherence, which is considered an important determinant of treatment inefficacy. Measurement of 6-thioguanine and 6-methylmercaptopurine nucleotides has been recently suggested as a screener for non-adherence detection. We describe four young patients in which non-adherence to azathioprine therapy was detected only through the measurement of drug metabolite concentrations, and the criterion for non-adherence was undetectable metabolite levels. After the identification of non-adherence, patients and their families were approached and the importance of a correct drug administration was thoroughly enlightened and discussed; this allowed obtaining a full remission in all subjects. Our observations support the use of undetectable metabolite levels as indicators of non-adherence to therapy in azathioprine treated patients. The additional level of medical supervision given by this assay allows getting a better adherence to medical treatment, which results in an improvement in the response to therapy; these benefits may justify the costs associated with the assay.
Keywords: 6-Mercaptopurine; Adolescent; Azathioprine; Child; Child, Preschool; Female; Guanine Nucleotides; Hepatitis, Autoimmune; Humans; Immunosuppressive Agents; Inflammatory Bowel Diseases; Male; Medication Adherence; Thionucleotides; Young Adult